Experimental production and chemical composition of Culex mosquito larvae and pupae grown in agro-industrial effluent - Habib, M. A. B.; Md. Yusoff, Fatimah; Phang, Siew Moi; Mohamed, Suhaila (Asian Fisheries Society, 2005)
An experiment was conducted to grow larvae and pupae of Culex mosquito in palm oil mill effluent (POME), latex concentrate rubber effluent and microalgae Selenastrum gracile (isolate no. 166) as cultured in 70 l tanks. No larval growth was observed in rubber effluent and very few larvae were found in microalgal tanks. Sampled Culex larvae and pupae grew in POME tanks, and were considered for biochemical analyses. The crude protein, real protein, lipid and ash content of Culex pupae were significantly higher (p < 0.05) than the larvae of the third and the fourth instars. All the essential amino acids of pupae except threonine, valine, isoleucine and lysine were significantly higher (p < 0.05) than those of the fourth instar followed by the third instar. The polyunsaturated fatty acids (PUFAs) of pupae such as linolenic acid (18: 3n-3), ¡-linolenic acid (18: 3n-6), arachidonic acid (20: 4n-6), eicosapentaenoic acid (22: 5n-3) and docosahexaenoic acid (22: 6n-3) were significantly higher (p < 0.05) than those of the third and the fourth instars. The pupae bioaccumulated significantly higher (p < 0.05) amount of essential minerals than larvae of the fourth instar followed by the third instar. The production of Culex pupae per 20 l of POME was 670 g, which is equivalent to 33.50 kg·ton-1. Due to presence of high micronutrients the larvae and pupae may be used as food for the rearing of post-larvae of 6-7 days old and fry of catfish, and shrimp and prawn. The presence of chitin as body covering of larvae and pupae helps to develop the chitinuous body covering of shrimp and prawn.